AB0455 Survival of prednisone-free remission in sle patients with serologically active clinical quiescent disease. (15th June 2017) - Nalotto, L; Ometto, F; Zen, M; Iaccarino, L; Gatto, M; Larosa, M; Doria, A
Abstract : Objectives: To evaluate survival of prednisone (PDN) – free remission in systemic lupus erythematosus (SLE) patients and to investigate the potential predictors of disease flares. Methods: Inclusion criteria were: (1) Diagnosis of SLE according to American College of Rheumatology (ACR) Classification Criteria of SLE; (2) Caucasian ethnicity; (3) Clinical remission (clinical SLEDAI-2K=0) at the time of PDN-withdrawal; (4) Stop of PDN treatment between 2010 and 2016; (5) At least two visits per year between January 2010 and April 2016. Disease activity was assessed according to SLE Disease Activity Index-2000 (SLEDAI-2K). Damage was measured by the SLICC/American College of Rheumatology Damage Index (SDI). Flares were defined according to Safety of Estrogens in Lupus Erythematosus National Assessment (SELENA)-SLEDAI criteria. We evaluated whether gender, age, age at PDN-stop, disease duration, duration of corticosteroid therapy, duration of remission before PDN withdrawal, time to flare, SLICC/American College of Rheumatology Damage Index (SDI) – score >3, positive anti-dsDNA antibodies (abs) and-or low C3/C4, type of SLE-involvement and concomitant immunosuppressive treatment could be predictors of flare. Multivariate logistic regression analysis was run to investigate the predictors of flare. Covariates included in the analysis were all variables reaching p<0.20 in the univariate analyses. Results: Among 400 patients evaluated, 104 (26%) fulfilled inclusion criteria. Baseline characteristics are reported in table 1 . Twenty-two (21.2%) patients flared. Mean time to flare was 19.91±13.14 months. Types of flare were 7 renal, 7 articular, 4 cutaneous, 2 haematological, 1 serositic and 1 neurological. Variables included in the multivariate logistic regression analysis were: positive anti-dsDNA abs and-or low C3/C4, skin, articular and haematological involvement. Skin involvement resulted predictive of flare (OR 3.07, 95% CI 1.11–8.53, P 0.031) as reported in table 2. Conclusions: In SLE patients who stopped corticosteroid therapy, previous skin involvement resulted to be a predictor of disease flare. Disclosure of Interest: None declared